Communicating climate : how to transmit your climate message and avoid greenwashing - Ross, Eleanor (Emerald Publishing Limited, 2023)
Businesses can no longer afford to stick their heads in the sand. The time to act is now. Cities are becoming unliveable, triggering migration patterns and resource shortages, in turn causing civil wars and conflict. Natural disasters like hurricanes and wildfires are simply becoming known as 'weather', and biodiversity is disappearing from our very eyes. The fact is, we won't have a planet to do business on if we don't act now. Climate change is already hitting our bottom lines, as the cost of natural resources, energy, and manpower skyrocket. It's predicted to cost the world $20 trillion a year if we can't keep global heating to less than 2 degrees Celsius. This is a book about communicating climate: how to achieve cut-through, whether you're trying to inspire your clients, get your shareholders on board, or simply showcase your progress in greening the world. This is not a greenwashing manual. It is about achieving balance in a world where we need to reduce our consumption, but also keep businesses functioning, just in a cleaner, greener, way. Communicating Climate is packed with case studies, examples, tips and interviews from those leading the charge towards sustainability.